Identifying drivers of change and predicting future land-use impacts in established farmlands. Issue 1 (2nd January 2022) - Wartenberg, A. C.; Moanga, D.; Butsic, V.
ABSTRACT: There is growing consensus that global food systems will need to undergo substantial transformations to ensure continued food security and to halt environmental degradation. Such efforts will have to include more sustainable management of existing farmscapes. Here, we examine drivers of cropland transitions between 13 crop commodities cultivated in Kern County, California. We parameterized multinomial logistic regression models of crop choices, using observed data from 2002 to 2018. We then simulated future crop choices under three scenarios exploring the consequences of climate change, water shortages and policy response, and projected impacts on three agroecosystem pressures (water-use, soil erosion, pesticide-use), and three agroecosystem services (profits, nutrition, and carbon sequestration). Agricultural land-use transitions were especially sensitive to biophysical factors, profits and neighborhood effects. Our results illustrate how climate change may lead to landscape-level crop replacement by 2050, with likely significant socio-ecological consequences.